Nomina agentis у Луцькій замковій книзі 1560–1561 рр.: семантика і структура - Павленко, Лариса; Pavlenko, Larysa (Східноєвропейський національний університет імені Лесі Українки, 2015)
Стаття є спробою проаналізувати особливості агентивних назв, уживаних у Луцькій замковій книзі 1560–1561 рр. Зокрема, докладно з’ясовано специфіку лексико-семантичної організації вказаних мовних одиниць, шляхи їхньої номінативної деривації. Розширено інформацію про ономасіологічні характеристики назв виконавців дії як досить розгалуженої з погляду семантики і структури макросистеми номенів. Установлено, що назви виконавців дії за способом їхньої діяльності, характером занять, особливостями професії, посад тощо є одним із найбагатших номінативних розрядів як щодо кількості лексем, так і щодо багатогранності дериваційних типів у межах ономасіологічної категорії особи. З’ясовано, що ядром цих мовних одиниць є віддієслівні похідні, а також від-іменні утворення, запозичення й складені найменування. Найпродуктивнішим способом номінативної деривації nomina agentis є афіксація (з використанням питомих і запозичених морфем). In this article the author attempts to analyze the peculiarities of the nomina agentis (names of agents who performed the actions) which were used in Lutsk castle book of 1560–1561. And in particular, the specific character of the lexical and semantic organization of these linguistic units, as well as the ways of their nominative derivation are clarified in detail. The information about the onomasio-logical characteristics of the names of agents who performed the actions has been expanded as a quite extensive in terms of semantics and structure macrosystem of nomenclatorial names. It has been established that nomina agentis by the way of their activity, occupation, as well as the peculiarities of their professions and positions is one of the richest nominative classes both in terms of the number of lexemes and the diversity of derivational types within the onomasiological category of a person. It has also been established that verbal derivatives, as well as nominal formations, borro-wings and compound names form the nucleus of these language units. Affixation (with the use of native and borrowed morphemes) turned out to be the most productive way of nominal derivation as far as nomina agentis are concerned.
Nomina Agentis in Lutsk Castle Book of 1560–1561: Se-mantics and Structure
Keywords: назви діяча; агентивні назви; ономасіологічні характеристики; типи номінативної деривації; nomina agentis (names of agents who performed the actions); onomasiological characteristics; types of nominal derivation